Implementasi Program Baznas dalam Pengembangan Sumber Daya Insani Studi Kasus pada BAZNAS Kabupaten Probolinggo - Sri Utami; Ratih Dwi Rahmawati; Muhammad Syarif Hidayatullah; Siti Lailaturrahmah; Septya Putri Utami; Tazi Al Quthubi; Yeni Kartikawati (Universitas Muhammadiyah Bengkulu, 2026)
This study aims to analyze the implementation of the National Zakat Agency (BAZNAS) program in Probolinggo Regency in developing human resources (SDI) through the productive management of zakat, infaq, and alms (ZIS). This research focuses on the changing role of BAZNAS from a charitable institution to a community empowerment institution. The study used qualitative methods through interviews, literature studies, and document analysis. The results indicate that the BAZNAS program encompasses three main areas: education, social humanity, and economic empowerment, which support community independence and well-being. From an Islamic economic perspective, this program reflects three dimensions of SDI development: tazkiyah (spiritual), tarbiyah (intellectual), and tamkin (economic). Despite its positive impact, program implementation still faces obstacles such as limited human resources, low productive zakat literacy, and a lack of synergy between institutions. Overall, BAZNAS Probolinggo Regency plays a strategic role in improving the spiritual, intellectual, and economic quality of the community and is a driving force in socio-economic development based on Islamic values.